If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 4 + x = 4 + -1x Reorder the terms: 4 + 3x + x = 4 + -1x Combine like terms: 3x + x = 4x 4 + 4x = 4 + -1x Add '-4' to each side of the equation. 4 + -4 + 4x = 4 + -4 + -1x Combine like terms: 4 + -4 = 0 0 + 4x = 4 + -4 + -1x 4x = 4 + -4 + -1x Combine like terms: 4 + -4 = 0 4x = 0 + -1x 4x = -1x Solving 4x = -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 4x + x = -1x + x Combine like terms: 4x + x = 5x 5x = -1x + x Combine like terms: -1x + x = 0 5x = 0 Divide each side by '5'. x = 0 Simplifying x = 0
| 36b+-10=-6 | | 45=5x-9+x | | -(1/7×3/2)= | | Y/10=9/4 | | 4c-16=8 | | -12u+7=-1 | | 3x^2-7x+3=2x^2-4x+3 | | j-3=7+6j | | 16/1 | | y^2-2xy+3=0 | | 7p-10=6p | | 5/50=t/4 | | 56y+5=13 | | 5/75=t/10 | | P/8=-51/24 | | 3/2=n/10 | | -14+49v=42 | | x^2=-54-15x | | 5/x=55/22 | | .5(8x-43+10)=2x | | 36+16u=52 | | -3(5z-12)= | | -x+179=229 | | 2/3(5x) | | 18x-3=20x-16 | | f(-7)=3y-5 | | 4(x+8)+x=12 | | f(y)=3y-5 | | 10x+20=2x-4 | | (4x-8)/(3)=4 | | 221=8-x | | 21+49x=7 |